Spatial Distribution of Human Development Index in the Regions of Russia - SHAMSUTDINOVA, Nailya K.; ISIANGULOVA, Elmira I.; LAKMAN, Irina A.; PRUDNIKOV, Vadim B.; SADIKOVA, Liana F. (Journal of Advanced Research in Law and Economics; Vol 8 No 8 (2017): JARLE, Volume VIII, Issue 8(30), Winter 2017, 2018)
Spatial effects in human development levels among different regions of a territory are important to study in the context of the core-periphery model. We use different methods to study human development index (HDI) for 85 Russian regions. The authors studied the human development index (HDI) for 85 Russian regions. Methods of spatial statistics (econometrics) are used to estimate the ‘spatial gradient’ in economic geography (Moran’s global and local I, Geary’s C, Getis-Ord global G indices). As a weighting matrix we used a contiguity matrix, taking into account the HDI levels only in neighboring regions. Analysis of the global indices of Moran’s I, Geary’s C and Getis-Ord G and Morans scatter plots showed the presence of time-inconsistent spatial autoregressive dependence of the level of HDI in regions of Russia. The ‘spatial gradient’ of the level of human development in Russia is influenced by historically existing imbalances (due to strong oil and gas export-oriented nature of the economy) and insufficient use of human capital. To our view the regional differentiation in human development among the regions is caused primarily by the ‘catching up’ style of Russian economy: human capital is concentrated in regions with already high level of development, although in terms of growth rates Moscow and St. Petersburg are not the leaders. The territorial and geopolitical policies of Russian Federation also influence HDI distribution. For example, huge public investments in the regions of Russian Far East are often ineffective.